Treatment and Effect of Loess Metro Tunnel under Surrounding Pressure and Water Immersion Environment. (13th June 2020) - Wang, Lixin; Li, Chenghan; Qiu, Junling; Wang, Ke; Liu, Tong; Li, Heng
Abstract : It is possible to pass through a collapsible loess stratum during metro tunneling. When the surrounding potential water sources with pressure are induced by external influences, the tunnel structure will be influenced in the affected area of loess collapsibility. To deal with the water inrush disaster of the tunnel in a collapsible loess stratum, the mechanism of grouting diffusion in the loess stratum is analyzed. It is found that the main influencing factors of the grouting effect are the radius of the grouting ring and the permeability coefficient of the grouting ring. Then, based on the water inrush section of a metro tunnel in Xi'an city, China, the treatment effect of the project is compared and analyzed through field tests, field monitoring, and finite element simulation. The results show that the water pressure at the measuring point of the tunnel vault is reduced by 4 MPa; the maximum and the minimum principal stresses at the top of the segment lining increased by 34.9 kPa and 8.8 kPa, respectively, which is less than the increase without grouting; and the maximum displacement of the surrounding rock is reduced by 19 mm. The plastic area produced by local water source infiltration is about 62% of that before grouting. The treatment measures of grouting in the tunnel are safe and effective. This study is of valuable meaning for the treatment of water inrush disaster of a loess tunnel under the water environment.